1998
DOI: 10.1046/j.1365-2141.1998.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Renin in acute myeloid leukaemia blasts

Abstract: Summary.Hypokalaemia is a clinical phenomenon in patients with acute myeloid leukaemia (AML) to which activation of the renin-angiotensin system (RAS) may contribute. Recently monocytes were found to express renin, the key initializing enzyme of the RAS. By RT/PCR, transcripts for renin were detected in four of 18 bone marrow samples from patients with AML. Three leukaemic cell lines, isolated monocytes, bone marrow stromal cells and 25 peripheral blood and 24 bone marrow samples of normal controls were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…For amplification of renin cDNA oligonucleotide primers and conditions were used as previously described [9]. Amplification of kidney RNA served as positive control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For amplification of renin cDNA oligonucleotide primers and conditions were used as previously described [9]. Amplification of kidney RNA served as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Wulf et al, have demonstrated that myeloid blast cells have renin in the cytosol [8] and recently they have also described that BM blast cells from some acute myeloid leukemia (AML) expressed renin [9]. This finding could be responsible for the activation of the RAS [8,10] and the presence of hypokalemia in 25 -59% of the untreated AML patients [10,11] which could be a mechanism protecting from the hyperkalemia usually associated to AML [12] In accordance with these results, we investigated the expression of renin in BM of patients with hematological malignancies and found a significant renin expression in cells from AML patients.…”
Section: Introductionmentioning
confidence: 97%
“…Renin-like enzyme activity converting ANGTS to Ang-I had been detected in leukemic blast cells. 24,25 Specific immunoreactive renin-like peptide of 47 kDa was isolated from AML blast cells. 24,25 Renin is expressed in some myeloid human leukemia cell lines such as K562, KU812 and MEG-01.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Specific immunoreactive renin-like peptide of 47 kDa was isolated from AML blast cells. 24,25 Renin is expressed in some myeloid human leukemia cell lines such as K562, KU812 and MEG-01. 9,18,26 Renin system is present in the K562 leukemic cell line in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the RAS component renin is expressed in the bone marrow microenvironment as well as in hematopoietic cells (Abali et al, 2002). Bone marrow blast cells of some types of AML (M4 and M5 FAB types) express renin (Wulf et al, 1998), however no expression has been detected in normal bone marrow from healthy donors (Gómez Casares et al, 2002). Our group also detected renin expression in AML patients, but it did not relate to monocytic dififerentiation or to the existence of other cytogenetic risk markers (Gómez Casares et al, 2002).…”
Section: Other Molecular Markers In Research: Renin Expressionmentioning
confidence: 99%